Czego chce Basia od polskiego społeczeństwa? - Cackowska Małgorzata (Wydawnictwo Uniwersytetu Gdańskiego, 2018)
This paper presents an analysis and critique of the representation of living spaces of the contemporary child in the hugely popular Polish series of picturebooks on the daily life of a little girl called Basia. The article describes the image of her family home primarily as a space which is significant for the development of a young person in its cultural, social, and political aspects, and finally tries to answer the question of what this (very popular) message wants from its readers, the Polish society? The question appearing in the title is a travesty of the title of the book What Do Pictures Want? by W.J.T. Mitchell, one of the most eminent researchers and theoreticians of the visual culture, who analysed various relations between the contemporary audience and representations present in images, searching for knowledge on the condition of today's viewer (Mitchell 2015). In conclusion, the critical approach to the series of books analysed in the text derives from sensitivity to noticing the phenomenon of a large range of politically unilateral power of reproduction of the models the books contain.